A new species of Oreophrynella (Anura: Bufonidae) from the Pantepui region of Guyana, with notes on O. macconnelli Boulenger, 1900 - Kok, Philippe J. R. (Zootaxa, 2009)
Oreophrynella seegobini sp. nov. is described from 2088 m elevation on Maringma tepui in the Pakaraima Mountains of Guyana, at the Guyana-Brazil border. The new species is mainly distinguished from known congeners by small size, indistinct frontoparietal crests, prominent postorbital crests, prominent suborbital crests, well-developed webbing on hand and foot, dorsal skin minutely spiculate with scattered medium to large elevated tubercles, ventral skin anteriorly rugose with few flat granules, posteriorly tuberculate, blackish brown dorsal colour, and dark brownish orange ventral colour. Data on four specimens of O. macconnelli collected on the southeast slope of the tepui are provided.